Peningkatan Pemahaman Membaca Teks Deskriptif Siswa Kelas VII melalui Strategi Bertanya 5W+1H - Tokan, Fitria; Pohan, Erwin; Sugianto (English Education Department, 2025)
The aims of this study was to increase students' reading comprehension of descriptive texts using the 5W+1H questioning strategy to address concerns identified in the classroom. This study focused on seventh-grade students, specifically those in class VII.2, which consisted of 34 individuals. The classroom action research (CAR) approach was used in this study. The data were collected using an observation checklist and tests. The researcher analyzed the data using a combination of qualitative and quantitative data, as well as the observation checklist. Furthermore, the researcher assessed the test based on the mean score for each cycle in qualitative data. Based on qualitative data, this study found that the 5W+1H questing approach and learning process increased students' classroom reading behavior. The observation checklist showed that the student's performance improved between the first and second cycles. The quantitative data results also demonstrated an improvement in the students' reading comprehension mean scores between the first and second cycles. The study suggests that implementing the 5W+1H questioning strategy can significantly improve students’ reading comprehension.